Faktor-Faktor yang Mempengaruhi Efektifitas Pengelolaan Dana Desa pada Desa-Desa di Mayong, Jepara - Prihasantyo Siswo Nugroho (The Academy Of Management and Business, 2022)
The management of village funds is a responsibility that must be carried out by the village government as the administrative actor, and also as the manager of village funds to the community  who benefit from the use of the village funds. Implementation of Transparency to the public is open about information to the public, and if the public needs this information, the public will immediately get it. With this openness, the managed village funds can be properly controlled and supervised by the authorities. While the implementation of accountability to the community must be carried out because it refers to the purpose of the existence of village funds, namely to improve community welfare, where these efforts can be carried out with community empowerment. This study uses a quantitative method with a descriptive approach. The results show that transparency has a positive and significant effect on the management of village funds. Likewise, accountability has a positive and significant effect on the management of village funds.